Accurate and precise optical phase sensor based on a nonlinear quantum Sagnac interferometer - Romain Dalidet; Laurent Labonté; Gregory Sauder; Sébastien Tanzilli; Anthony Martin (Physical Review Research)
Optical phase measurements play a key role in the detection of macroscopic parameters such as position, velocity, and displacement. They also permit to qualify the microscopic properties of photonic waveguides such as polarization mode dispersion, refractive index difference, and chromatic dispersion. In the quest for ever-better measurement performance and relevance, we report a quantum nonlinear interferometer based on a Sagnac configuration allowing precise, accurate, self-stabilized, and reproductible optical phase measurement. The potential of this system is demonstrated through the measurement of second-order dispersion, namely, chromatic dispersion of a commercial dispersion-shifted fiber at telecommunication wavelength. We demonstrate a precision of 0.007%, surpassing state-of-the-art measurements by more than one order of magnitude. Additionally, the accuracy of the second-order dispersion value is determined through the measurement of the third-order dispersion, showing a quadratic error as low as 5%. Our system promises the development of photonic-based sensors enabling the measurements of optical-material properties in a user-friendly manner.